Efektifitas Konseling Dengan Metode Demonstrasi Cara Menyikat Gigi Sebagai Upaya Meningkatkan Pengetahuan Dan Keterampilan Menyikat Gigi Pada Anak - Saleh, Muhammad; Asriawal; Sainuddin; Rahma , Nur (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Dental and oral health problems in elementary school children are still quite high, one of which is caused by the lack of knowledge and skills of proper tooth brushing. This study aims to determine the effectiveness of counseling with a demonstration method on how to brush teeth in improving knowledge and skills of tooth brushing in Gunung Sari II Elementary School students. The type of research used is a Quasi Experiment with a Pre-test and Post-test One Group Design. The sample of the study was 55 students in grades IV, V, and VI who were taken using a total sampling technique. Data collection was carried out through a questionnaire on knowledge and skills of tooth brushing before and after counseling with the demonstration method. Data analysis used the Wilcoxon Signed Rank Test. The results of the study showed a significant increase in students' knowledge and skills after counseling with the demonstration method. Before the counseling, most students were in the category of sufficient knowledge (58%) and sufficient skills (56%). After the counseling, most students improved to the good category (84% for knowledge and more than 70% for skills). Counseling using the demonstration method has proven effective in improving students' knowledge and skills in brushing their teeth, and can be used as a dental health education strategy in schools through the UKGS program with the support of teachers and parents.